Bycatch levies could reconcile trade-offs between blue growth and biodiversity conservation - Booth, H; Arlidge, W; Squires, D; Milner-Gulland, E (Springer Nature, 2021)
Economic activities in the ocean (i.e. the ‘blue economy’) provide value to society, yet also jeopardise marine ecosystems. For example, fisheries are an essential source of income and food security for billions of people, yet bycatch poses a major threat to marine biodiversity, creating trade-offs between economic growth and biodiversity conservation. This paper explores bycatch levies as a market-based instrument for reconciling these trade-offs. We outline the theory and practice of bycatch levies, to demonstrate how they could incentivise bycatch prevention and raise revenue for compensatory conservation, provided they are well-designed, as part of a policy mix for sustainable and equitable ocean governance. We then explore ways forward for mainstreaming bycatch levies in to the blue economy. While compensatory bycatch mitigation has been controversial, increasing adoption of net outcome approaches to biodiversity conservation suggests they could become mainstreamed within the next decade. Bycatch levies could raise millions of dollars towards closing global biodiversity financing gaps; delivering net outcomes for biodiversity under the UN Biodiversity post-2020 framework whilst enabling blue growth, and moving towards win-wins for economic welfare and biodiversity conservation.